Using the local environment for outcomes-based education: issues raised for INSET by teachers' perceptions of agents of change - Burton, Noreen (Rhodes University, Faculty of Education, Department of Education, 1998)
South African education is in the process of undergoing what has become known as a "paradigm shift", requiring a change from the familiar transmission method to outcomes-based education (OBE) founded on social constructivist theories oflearning and teaching. Teachers, (45% of whom are poorly qualified), "will play a pivotal role in the success or failure of this change. There is therefore an urgent need to re-educate in-service teachers in the philosophy, and related methodologies underpinning Curriculum 2005. To this end, in-service education courses need to be developed "which will encourage teachers to reconstruct their beliefs about teaching and learning. INSET programmes in the past were aimed at either "topping up" qualified teachers, or "adding on" for under qualified teachers - neither of which have proved successful. It is therefore unlikely that applying similar methodologies to support teachers in the shift to OBE will meet with success, nor will simply "training" teachers to use the new learning programmes. Government documents on Education Policy are calling for teachers to become reflexive practitioners, able to guide learners in their efforts to achieve the critical outcomes which are intended to develop a competent citizenry of lifelong learners. Therefore, teachers ought to be empowered as curriculum developers in their own right. This interpretative case study hoped to find out from teachers themselves what aspects of an activity-based environmental education course acted as change agents in assisting them to begin the shift to constructivist theories of teaching and learning. A variety of research tools were used, including questionnaires, interviews, journals, narratives and concept maps, all of which provided a rich source of data for interpretation. From what was gained from four participants in this research, tentative suggestions for incorporation into the next cycle of action research in future INSET programmes are made.
Keywords: In-service education and training for teachers; Teachers -- Training of -- South Africa; Teachers -- In-service training -- South Africa; Competency-based education -- South Africa